How does consumer-to-consumer community interaction affect brand trust? - Tabish, Muhammad; Yu, Zhang; Thomas, George; Rehman, Syed Abdul; Tanveer, Muhammad (Frontiers in Environmental Science, 2022)
This article seeks to study how the extensive usage of social networking sites (SNSs) and interaction in consumer-to-consumer (C2C) communities influence brand trust. Social networking sites have impacted internet commerce in this technologically advanced era. It connects global users. Social media ads have changed our thinking; new market trends are reshaping the business industry. This study empirically investigates a model based on media richness theory and social capital theory. Using data collected from users who conducted transactions on these sites, a theoretical model was developed to analyze the inspirations behind trust. The results show that Instagram’s media-rich platform enhances social capital and a sense of virtual community between its members, affecting trust. Instagram usage intensity does not immediately affect brand trust, but it has an indirect effect; community trust also positively influences brand trust. This study defines the role of a sense of virtual community (SOVC) and social capital in C2C communities. This study delivers insights to managers on social networking sites with crucial new insights on how to increase brand trust via SNSs. Prior studies on social commerce do not apply to C2C communities on social media platforms, especially Instagram. This study presents a novel standpoint of social capital and media richness structures as precursors of brand trust in C2C communities.